2013
DOI: 10.1038/pr.2013.45
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of white matter injury following neonatal stroke with serial DTI

Abstract: Background: Diffusion tensor imaging (DTI) can be used to predict outcome following perinatal arterial ischemic stroke (PAIS), though little is known about white matter changes over time. Methods: Infants with PAIS were serially scanned in the neonatal period (n=15), at 3 months (n=16), and at 24 months (n=8). FA-values in five regions of interest (anterior and posterior limb of the internal capsule, corpus callosum, optic radiation and posterior thalamic radiation) were obtained and compared with FA- values… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 30 publications
6
16
0
Order By: Relevance
“…17 A DTI study by van der Aa et al showed that fractional anisotropy values, while not initially lower after injury, do reflect functional pathway disruption at 3 months after perinatal stroke, and this alteration predicts cortical dysfunction in motor and visual pathways. 37 Our data seem to support this supposition, in that only 3 of 11 stroke patients showed normal contralateral sensorimotor activation on fMRI-the same 3 perinatal stroke patients with severe motor decline postoperatively.…”
Section: Predicting Motor Preservation After Hemispherectomysupporting
confidence: 63%
“…17 A DTI study by van der Aa et al showed that fractional anisotropy values, while not initially lower after injury, do reflect functional pathway disruption at 3 months after perinatal stroke, and this alteration predicts cortical dysfunction in motor and visual pathways. 37 Our data seem to support this supposition, in that only 3 of 11 stroke patients showed normal contralateral sensorimotor activation on fMRI-the same 3 perinatal stroke patients with severe motor decline postoperatively.…”
Section: Predicting Motor Preservation After Hemispherectomysupporting
confidence: 63%
“…Substantial efforts has been devoted to establish human normative maturation curves of diffusion indices in specific WM tracts (Dubois et al, 2008a; Geng et al, 2012; Sadeghi et al, 2013) with the hope that deviation of an individual subject data from a normative maturation curve would indicate injury(van der Aa et al, 2013) or developmental abnormalities (Prastawa et al, 2010). Such an approach definitely holds promise during rapid myelination period in the first 1-2 years of infancy when the magnitude of diffusion changes is large (Mukherjee et al, 2001; Sadeghi et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Such an approach definitely holds promise during rapid myelination period in the first 1-2 years of infancy when the magnitude of diffusion changes is large (Mukherjee et al, 2001; Sadeghi et al, 2013). The link between rapid diffusion indices change and early myelination phase may explain why FA measurements at 3 month infants were found to be a more reliable predictor of neurodevelopmental outcome than in neonates after neonatal stroke (van der Aa et al, 2013). This is probably because of myelination being in rapid dynamic phase at 3 months and at this time, DTI indices are more sensitive to injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In studies drawing subjects from the same longitudinal study [1][2][3], only the most recent data were reported. In studies using the same data [4][5][6], only the most recent and largest studies were reported. (Table 1) There are a wide range of visual abnormalities seen in perinatal stroke survivors (Table 1); 136 children were included.…”
Section: Resultsmentioning
confidence: 99%